Impact of fruit peels extract on the shelf-life of minced beef - Ahmed, Asmaa R.; Abd Elhameed, Ghada A. (Journal of Advanced Veterinary Research, 2024)
Fourteen kilograms of minced meat were divided into 4 groups (about 3.5 Kg for each group). All samples were examined to study the effect of the addition of 1% fruit peel extracts (banana, orange, and pomegranate) on the extension of the shelf life of such food article. Reduction of APC after 6 days in samples treated with banana, orange, and pomegranate peel reached 83.9 %, 91.6 %, and 95.4%, respectively and reduction of articles coliform reached 75.8%, 90.3 %, and 93% while S. aureus count reduced by 77.5%, 89%, and 96.5 %, respectively. Fruit peels decreased pH values compared with the control sample during storage at 4ËšC for 10 days. pH values of samples treated with banana peel decreased from 5.63 to 5.61 at zero time and from 6.71 to 5.84 on the 6th day and orange peel decreased to 5.58 and to 5.70 while pomegranate to 5.56 and to 5.67 at zero time and at 6th day of storage, respectively. TVB-N values of samples treated with banana decreased from 1.97 to 1.89 at zero time and from 29.58 to 9.83 on the 6th day and orange peel decreased to 1.84 and to 7.90 while pomegranate to 1.81 and to 6.88 at zero time and at 6th day. TBA values of samples treated with banana peel decreased from 1.22 to 0.25 on the 6th day but orange peel decreased to 0.02 and to 0.19 and with pomegranate to 0.02 and to 0.14 at zero time and on the 6th day of storage, respectively. In general, the incorporation of banana, orange, and pomegranate peel powder into minced meat as natural preservatives improved color, odor, appearance, consistency, and overall acceptability and extended their shelf life during storage.